Utilization of golden1000 application for exclusive breastfeeding success in stunting prevention efforts - Imaniar, Melsa Sagita; Nurdianti, Dewi; Rahmah, Aulia (Alma Ata University Press, 2024)
Background :Stunting is a developmental growth disorder experienced by children due to poor nutrition, recurrent infections, inadequate psychosocial stimulation, and the child's height for his age is below the average of SD STKA WHO. Indonesia has a prevalence of 36.4%. Stunting prevention involves priority interventions, namely specific nutrition interventions and sensitive interventions. Exclusive breastfeeding, including specialized interventions, plays a very important role in preventing stunting. Indonesia's Health Profile in 2019, Indonesia's exclusive breastfeeding coverage is 37.3%, while the national target is 80%, West Java 57.9% and Tasikmalaya City 56.0%, of course this will cause problems in the future related to stunting events, especially in cities. Tasikmalaya. The current problem is the low access to information obtained by mothers in increasing knowledge and literacy about breastfeeding. As an innovative product, it is used as an educational medium about breastfeeding preparation, breastfeeding attachment positions, problems and solutions in breastfeeding, breastfeeding tutorial videos and breastfeeding management as well as online consultations with breastfeeding counselors. Objectives : The purpose of this study is the influence of the golden1000 application to increase maternal efficacy literacy related to breastfeeding so that it can be successfully breastfed exclusively. Methods : This study uses a quasi-experimental design method, with a posttest only control group design approach. In this study, the treatment group was given an intervention in the form of the golden1000 menu application about breastfeeding including an educational menu about breastfeeding, video tutorials on attachment positions and an online consultation feature with a breastfeeding counselor for pregnant women in the third trimester up to 6 months of breastfeeding. Results : The results of the study found that there was a statistically different difference in the success of exclusive breastfeeding between the golden1000 application group and the KIA book group.Conclusions : The use of the golden1000 application can increase the success of breast milk givers exclusively.